2007
DOI: 10.1111/j.1460-9568.2007.05361.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a transneuronal cytokine family Cbln − regulation of secretion by heteromeric assembly

Abstract: Cbln1, a member of the C1q and tumor necrosis factor superfamily, plays crucial roles as a cerebellar granule cell-derived transneuronal regulator of synapse integrity and plasticity in Purkinje cells. Although other Cbln family members, Cbln2-Cbln4, have distinct spatial and temporal patterns of expression throughout the CNS, their biochemical and biological properties have remained largely uncharacterized. Here, we demonstrated that in mammalian heterologous cells, Cbln2 and Cbln4 were secreted as N-linked g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
84
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 24 publications
5
84
0
Order By: Relevance
“…1-4). Although the precise role of Cbln3 in vivo remains unclear, one of its putative functions is the negative regulation of the release of Cbln1 through the formation of Cbln1-Cbln3 heteromers, which are mostly retained in the soma (Iijima et al, 2007). Interestingly, the high-K ϩ -induced repression of cbln3 mRNA was slightly but significantly delayed by that of cbln1 mRNA (Fig.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1-4). Although the precise role of Cbln3 in vivo remains unclear, one of its putative functions is the negative regulation of the release of Cbln1 through the formation of Cbln1-Cbln3 heteromers, which are mostly retained in the soma (Iijima et al, 2007). Interestingly, the high-K ϩ -induced repression of cbln3 mRNA was slightly but significantly delayed by that of cbln1 mRNA (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Cultured cerebellar granule cells were lysed with buffer (10 mM Tris-HCl, pH 8.0, 100 mM NaCl, 1 mM EDTA, 1% Triton X-100) containing 0.1% SDS and a protease inhibitor mixture mix (Roche Applied Science), and the soluble fractions were analyzed by immunoblotting with anti-Cbln1 or anti-Cbln3 antibody (rabbit; 1:250), which were kindly provided by Dr. Masahiko Watanabe (Hokkaido University, Sapporo, Japan) (Iijima et al, 2007;Miura et al, 2009). Horseradish peroxidase-conjugated secondary antibody and the enhanced chemiluminescence kit (both from GE Healthcare) were used for these analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Cbln3 binds specifically to Cbln1 (6) and recently Cbln4 was identified (7) (NCBI accession number NM_175631). All members of the Cbln family form homomeric and also heteromeric complexes with each other in vitro and it was suggested that such complexes play a crucial role in normal development of the cerebellum (2,8). However, not only entire Cbln molecules are able to act as a transneuronal cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…At present, Cbln are recognized as a new class of transneuronal regulators of synapse development and synaptic plasticity in various brain regions (6,8). With great probability this action depends on direct paracrine effects of Cbln complexes on adjacent synapses or nervous cells.…”
Section: Introductionmentioning
confidence: 99%
“…Precerebellins belong to the C1q/TNF superfamily of secreted proteins and, like other members of the family, they may form homomeric and also heteromeric complexes with each other in vitro (6)(7)(8)(9)(10)(11)(12). At present, Cbln are recognized as a new class of transneuronal regulators of synapse development and synaptic plasticity in various brain regions (6,8).…”
Section: Introductionmentioning
confidence: 99%